Silica's Medium in Various Concentration Effect on Navicula sp. Metabolism - Karillanata, Khalid Erlangga; Luthfiana, Dwi Hardianti; Maghfiroh, Khusnul Qonita; Kurnianto, Dedy; Amelia, Ria; Erfianti, Tia; Suyono, Eko Agus (Al-Kauniyah: Jurnal Biologi, 2025)
Abstract Navicula sp., an aquatic microalgae species, are numerous and diverse, with high metabolites so they hold great potential in biotechnology. Although it has many advantages, it is often not used in industry. In silica medium, Navicula sp. produces various metabolites depending on their concentration. This research aims to discover how adding silica to the medium affects the growth and production of Navicula sp. metabolites so that cultivation can be carried out at low cost and with maximum results. For 21 days, this experiment was carried out with three concentrations of silica (1; 1.5; and 2 mL/L) and one control (0 mL/L) grown each in a 500 mL culture of Navicula sp. Repetition was done thrice for each measurement parameter; growth speed, biomass production, lipids, carbohydrates, and protein. Medium silica 1.5 mL/L was the optimal concentration for growth speed, biomass production, and carbohydrate production for Navicula sp. (0.083; 0.54; and 0.075 mg/day, respectively). Meanwhile, the optimal silica concentration for lipid and protein production for Navicula sp. were 1 mL/L medium and control medium (0.517 and 0.8 × 10-2 mg/day, respectively). Overall, this research can be used to grow Navicula sp. in producing specific metabolites optimally. AbstrakNavicula sp., spesies mikroalga akuatik, sangat banyak dan beragam dengan metabolit yang tinggi, sehingga memiliki potensi yang besar dalam bioteknologi. Meskipun memiliki banyak keunggulan, spesies ini seringkali tidak digunakan dalam industri. Dalam medium silika, Navicula sp. menghasilkan berbagai metabolit tergantung pada konsentrasinya. Tujuan dari penelitan ini adalah untuk mengetahui bagaimana penambahan silika dalam medium memengaruhi pertumbuhan dan produksi metabolit Navicula sp., sehingga kultivasi dapat dilakukan dengan biaya yang rendah dan hasil yang maksimal. Selama 21 hari, eksperimen ini dilakukan dengan tiga konsentrasi silika (1; 1,5; dan 2 mL/L) dan satu kontrol (0 mL/L) yang ditumbuhkan di dalam 500 mL kultur Navicula sp. Pengulangan dilakukan tiga kali untuk setiap parameter pengukuran, yaitu kecepatan pertumbuhan, produksi biomassa, lipid, karbohidrat, dan protein. Medium silika 1,5 mL/L merupakan konsentrasi yang optimal untuk kecepatan pertumbuhan, produksi biomassa, dan produksi karbohidrat bagi Navicula sp. (0.083; 0.54;  dan 0.075 mg/hari, secara berurutan). Sementara itu, konsentrasi silika yang optimal untuk produksi lipid dan protein bagi Navicula sp., secara berurutan, adalah medium 1 mL/L dan medium kontrol (0.517 dan 0.8 × 10-2 mg/hari). Secara keseluruhan, penelitian ini dapat dijadikan sebagai solusi untuk menumbuhkan Navicula sp. dalam memproduksi metabolit tertentu secara optimal.